Pengaruh Fee Audit, Audit Tenure, dan Rotasi Audit terhadap Audit Report Lag: Implikasi bagi Efisiensi Audit dan Ketepatan Waktu Laporan - Pakpahan, Ramses; Abbas, Dirvi Surya (Universitas Muhammadiyah Bengkulu, 2025)
This study examines the influence of Audit Fee, Audit Tenure, and Audit Rotation on Audit Report Lag, focusing on manufacturing companies in the property and real estate sector listed on the Indonesia Stock Exchange during the 2017–2021 period. The research is motivated by the importance of timely financial reporting, which significantly impacts stakeholders' decision-making processes. However, prolonged Audit Report Lag remains a challenge, and limited studies have addressed its relationship with these audit variables, creating a gap in the literature. This study employs panel data regression analysis on data from 33 companies over the five-year period, resulting in 165 observations. Secondary data were obtained from audited financial statements and corporate disclosures. The findings reveal that Audit Fee and Audit Tenure have a significant negative effect on Audit Report Lag, indicating that higher fees and longer auditor-client relationships can expedite reporting. Conversely, Audit Rotation shows a positive relationship with Audit Report Lag, suggesting that auditor changes may delay reporting. These findings provide valuable insights for regulators, auditors, and companies to enhance the efficiency and timeliness of audits